Differential gene expression in neonatal calf muscle tissues from Hanwoo cows overfed during mid to late pregnancy period - Borhan Shokrollahi; Myungsun Park; Youl-Chang Baek; Shil Jin; Gi-Suk Jang; Sung-Jin Moon; Kyung-Hwan Um; Sun-Sik Jang; Hyun-Jeong Lee (Scientific Reports)
Abstract Maternal nutrition significantly influences fetal development and postnatal outcomes. This study investigates the impact of maternal overfeeding during mid to late pregnancy on gene expression in the round and sirloin muscles of Hanwoo neonatal calves. Eight cows were assigned to either a control group receiving standard nutrition (100%) or a treated group receiving overnutrition (150%). After birth, tissue samples from the round and sirloin muscles of neonatal calves were collected and subjected to RNA sequencing to assess differentially expressed genes (DEGs). RNA sequencing identified 43 DEGs in round muscle and 15 in sirloin muscle, involving genes related to myogenesis, adipogenesis, and energy regulation. Key genes, including PPARGC1A, THBS1, CD44, JUND, CNN1, ENAH, and RUNX1, were predominantly downregulated. Gene ontology (GO) enrichment analyses revealed terms associated with muscle development, such as “biological regulation,” “cellular process,” and “response to stimulus.” Protein-protein interaction networks highlighted complex interactions among DEGs. Random Forest analysis identified ARC, SLC1A5, and GNPTAB as influential genes for distinguishing between control and treated groups. Overall, maternal overnutrition during mid-to-late pregnancy results in the downregulation of genes involved in muscle development and energy metabolism in neonatal Hanwoo calves. These findings provide insights into the molecular effects of maternal nutrition on muscle development.